Pengaruh Reward dan Disiplin Belajar Terhadap Hasil Belajar Siswa - Dian Afrilisa; Rose Rahmidani (Universitas Negeri Padang, 2023)
This study aims to determine and analyze the effect of rewards and learning discipline on student learning outcomes in economics subjects at SMAN 7 Padang. This type of research is descriptive associative learning. The population in this study were students of SMAN 7 Padang. The sample used was 269 students of SMAN 7 Padang and used proportional random sampling. Primary data are the kinds of data utilised in this research. Data processing uses SPSS 25. A questionnaire is the technique employed for data collection. The collected data was examined using descriptive analysis. Analysis of multiple regression in research. Considering the research's findings it is known that rewards and learning discipline have an important impact on how well students learn economics at SMAN 7 Padang with Sig 0.004 <0.05, At SMAN 7 Padang, incentives have a significant impact on students economics learning results with a value of Sig 0.005<0.05, at SMAN 7 Padang, the discipline that students learn significantly affects on their results of learning in economics.with Sig 0.000<0.05.